Penerapan Manajemen Peserta Didik dalam Upaya Meningkatakan Kedisiplinan Siswa - Siti Nurhidayatul Hasanah; M. Riza Zainuddin (DIMAR: Jurnal Pendidikan Islam, 2022)
The institution's efforts to make good student achievement and discipline are the main factors in it because it trains students to be able to control themselves, respect, and obey all the rules and regulations that exist in the school. However, on the contrary, violations or deviations from the order will harm him and will cause a problem, so that in its implementation as education, it can take action against students by being given sanctions or punishments and warnings.Punishment should not be carried out unless it has been preceded by a warning. In giving punishment, the teacher should pay attention to the following things: punishment must have something to do with mistakes, punishment must be adjusted to the child, punishment must be given fairly and the teacher is able to forgive students after the punishment is given.